Psychrophiles: Ecological significance and potential industrial application - Hamdan, Amira (South African Journal of Science, 2018)
The bulk of earth’s biosphere is cold (5 °C) that sustains a broad diversity of microbial life by triggering physiological response(s) to ensure survival in cold and frozen ecosystems. The strategy of adaptation to cold environments includes changes in membrane composition and induction of a set of specific cold-active proteins, polyunsaturated lipids and exopolysaccharides. These adaptive features provide an enormous natural reservoir of enzymes that function effectively in cold environments, and these coldactive enzymes have been targeted for innovative applications useful to humankind. This review provides an overview of the existence, distribution and adaptation strategies of psychrophilic microorganisms worldwide with great emphasis on their recently emerged industrial applications in the textile industry, food and dairy industry, brewing and wine industry, laundry detergent industry, and others. The bulk of earth’s biosphere is cold 5 °C that sustains a broad diversity of microbial life by triggering physiological response(s) to ensure survival in cold and frozen ecosystems. The strategy of adaptation to cold environments includes changes in membrane composition and induction of a set of specific cold-active proteins, polyunsaturated lipids and exopolysaccharides. These adaptive features provide an enormous natural reservoir of enzymes that function effectively in cold environments, and these coldactive enzymes have been targeted for innovative applications useful to humankind. This review provides an overview of the existence, distribution and adaptation strategies of psychrophilic microorganisms worldwide with great emphasis on their recently emerged industrial applications in the textile industry, food and dairy industry, brewing and wine industry, laundry detergent industry, and others.Significance:• The outcome of these studies may also help in the exploration of the possibility of life in distant frozen planets.